The nineteenth century in Machado de Assis's eyes - Alvarez, Audora Gedra Ruiz (ITINERÁRIOS – Revue de Littérature, 2010)
The aim of this study is to analyze the process of creating parody in the narrative “O sermão do Diabo”, by examining the means through which the narrator confronts the enunciative voice with the instituted discourse – Matthew’s “The sermon on the mount”. We will also observe that in this ideological clash, a playful space is forged and, in it, plurisignifi cation leads to the transgression of the pre-established code and, at the same time, the de-construction of the base-text is promoted and an ethos is rebuilt, in which the materialistic view of capitalism becomes a target of Assis’s irony and best humour.